Optimization Strategy for 5C Principles, 7P Principles, and 3R Principles in Banking Law - Kusuma Jala Wibowo, Brian; Roswandi, Agus; Evathia, Rena; Firmansyah; Siswajanthy, Farahdinny (PUSAT SAINS INDONESIA, 2024)
This research examines the introduction of the 5C, 7P and 3R principles in banking law. This research uses legal data, namely primary legal evidence and secondary legal evidence. This research focuses on library research, which means diving deeper into the applicable laws and regulations. Principles in banking law are very important, considering that a principle is a guideline to help the running of a bank, principles are regulated in banking law, so that a bank can have rules or confidence in the bank itself.